Reduced incidence of maternal health conditions associated with the home-based newborn care intervention package in Rural Gadchiroli, India: a 13 years before – after comparison - Anand A Bang; Abhay T Bang; Rani Bang; Mahesh Deshmukh; Kalindi Soni; Sanjay Baitule (Journal of Global Health Reports)
# Background